The Influence Of Transformational Leadership Intrinsic Motivation and Work Discipline On Employee Perfomance - Janah, Hikmah Nur; Herawati, Linda Puspita; Sulistiyowati, Lisa Harry (LPPM of NAROTAMA UNIVERSITY, 2024)
Design/methodology/approach: This type of research uses a quantitative approach and uses primary data. The population in the study was 110 employees of the Cirebon Regency Secretariat. The sampling technique in this research uses saturated samples, namely a sampling technique that uses all population members as samples—data collection through questionnaires. The analysis method used is the Statistical Product and Service Solution (SPSS) Version 25 method. Findings: The results of this study show that transformational leadership affects employee performance, intrinsic motivation affects employee performance, and work discipline affects employee performance. Research limitations and implications: This research focuses on the influence of transformational leadership, intrinsic motivation, and work discipline on employee performance. Practical implications: Based on the research results of the three variables, namely transformational leadership, intrinsic motivation, and work discipline, both directly and indirectly, it turns out that they simultaneously influence employee performance. Based on the research results, variable transformational leadership, intrinsic motivation, and work discipline have a joint (simultaneous) effect on employee performance at the Cirebon Regency Secretariat. Originality/value: This paper is original. Paper type: research paper Keywords: transformational leadership, intrinsic motivation, work discipline, employee performance.